2018
DOI: 10.1007/s10915-017-0637-y
|View full text |Cite
|
Sign up to set email alerts
|

High-Order Numerical Methods for 2D Parabolic Problems in Single and Composite Domains

Abstract: In this work, we discuss and compare three methods for the numerical approximation of constant-and variable-coefficient diffusion equations in both single and composite domains with possible discontinuity in the solution/flux at interfaces, considering (i) the Cut Finite Element Method; (ii) the Difference Potentials Method; and (iii) the summationby-parts Finite Difference Method. First we give a brief introduction for each of the three methods. Next, we propose benchmark problems, and consider numerical test… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 81 publications
(254 reference statements)
0
11
0
Order By: Relevance
“…We have chosen the finite difference method for the spatial discretization because of the simple geometric feature for one dimensional problems. Other numerical methods, such as the finite element method, the finite volume method, and the difference potential method can however also be used [25].…”
Section: Solving the Concentration Distributionmentioning
confidence: 99%
“…We have chosen the finite difference method for the spatial discretization because of the simple geometric feature for one dimensional problems. Other numerical methods, such as the finite element method, the finite volume method, and the difference potential method can however also be used [25].…”
Section: Solving the Concentration Distributionmentioning
confidence: 99%
“…Equations (30) and (31) were nonpositive so that (28) satisfied the energy estimate. Using the SMF, the energy analysis could be simplified to a large extent as a generic system.…”
Section: Continuous Energy Analysismentioning
confidence: 99%
“…e SBP-SAT method can develop strictly stable proof using the energy method, leading to robustness in spatial and time domains. Some review papers of SBP operators can be found in [25,26] and examples of SBP-SAT can be found in [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…For the time being, we will consider the PKS chemotaxis model in a spherical domain, but the proposed methods can be extended to more general domains in 3D (and the main ideas of the algorithms stay the same). We employ a finite-volume-finite-difference scheme as the underlying discretization of the model (1) in space, combined with the idea of Difference Potentials Method ( [41] and some very recent work [3,13,14,34], etc. ), that provides flexibility to handle irregular domains accurately and efficiently by the use of simple Cartesian meshes.…”
Section: An Algorithm Based On Dpmmentioning
confidence: 99%
“…Therefore, to construct a unique solution to BEP (19), we need to supply the BEP (19) with zero Neumann boundary conditions for the density and concentration. To impose boundary conditions efficiently into BEP, we will introduce the extension operator (21) below, similarly to [3,13,14,34], etc.…”
Section: Construction Of the Difference Potentialsmentioning
confidence: 99%